1996
DOI: 10.2165/00003088-199631040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics and Metabolism of Chloroquine

Abstract: This paper presents the current state of knowledge on chloroquine disposition, with special emphasis on stereoselectivity and microsomal metabolism. In addition, the impact of the patient's physiopathological status and ethnic origin on chloroquine pharmacokinetics is discussed. In humans, chloroquine concentrations decline multiexponentially. The drug is extensively distributed, with a volume of distribution of 200 to 800 L/kg when calculated from plasma concentrations and 200 L/kg when estimated from whole b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
237
1
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(255 citation statements)
references
References 118 publications
8
237
1
9
Order By: Relevance
“…Preliminary pharmacokinetic data indicate that more than 60% of compounds are bound to the corpuscular blood fraction. This is consistent with what has been described previously for CQ [4].…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Preliminary pharmacokinetic data indicate that more than 60% of compounds are bound to the corpuscular blood fraction. This is consistent with what has been described previously for CQ [4].…”
Section: Introductionsupporting
confidence: 93%
“…Preliminary pharmacokinetic data indicate that more than 60% of compounds are bound to the corpuscular blood fraction. This is consistent with what has been described previously for CQ [4].Since the early 1970s, the capacity of red blood cells (RBC) uninfected or infected by different strains of Pf to bind CQ or other aminoquinoline antimalarial drugs has been evaluated using 3 H-or 14 C-labeled compounds. The uptake of the drug by RBC was quantified by counting the radioactivity that is associated with the cell pellet or that disappeared from the incubation medium after centrifugation [5][6][7].…”
supporting
confidence: 83%
“…The extensive distribution of chloroquine has been attributed to its amphiphilic nature, which allows for lysosomal trapping. 11 The mechanism by which chloroquine induces lipidosis in tissues remains unknown. In vitro studies in Madin Darby canine kidney cells have shown chloroquine to be a potent inhibitor of lysosomal phospholipase A and C, suggesting a block in intralysosomal phospholipid catabolism as a possible explanation for the resulting lipidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Slow, rate-controlled intravenous infusion, is an acceptable mode of CQ administration in seriously illpatients or where oral therapy is not possible (Looareesuwan et al, 1986;Edwards et al,1987). CQ is generally well tolerated (Ducharme et al, 1996). The main adverse effects reported after therapeutic or prophylactic regimens include nausea, vomiting, abdominal discomfort, diarrhea, headache, blurred vision, lightheadedness, and fatigue.…”
Section: Chloroquinementioning
confidence: 99%